ELEVATING EFL LEARNERS’ VOCABULARY MASTERY THROUGH EDUCANDY GAME: A CLASSROOM ACTION RESEARCH STUDY - Ahmad Thoyyib Shofi; Tanzilun Ni'mah (J-Shelves of Indragiri (JSI), 2024)
Indonesian students often struggle to master English vocabulary due to limited exposure to the language. Effective teaching strategies that cater to students’ needs are crucial for vocabulary acquisition. This study investigates the use of the Educandy game to enhance vocabulary mastery among eleventh-grade students at MA Ihyaul Islam during the second semester of the 2023/2024 academic year. Employing the collaborative classroom action research (CAR) model by Kemmis and Taggart, the study was conducted over two cycles with 20 eleventh-grade students. The researcher collaborated with an English teacher in planning, implementing, observing, and reflecting on the game-based learning sessions. Various instruments were used, including observation sheets to monitor game implementation, interviews to explore related issues, and field notes to document all research activities. The findings indicate that the Educandy game significantly improved vocabulary mastery among the students. This digital tool engaged and motivated the learners, fostering active participation in vocabulary learning. All students met the minimum completion criteria in both cycles. The CAR approach facilitated continuous improvements based on observations, enhancing the overall effectiveness of the study.